Cytotoxic Polyprenylated Benzoylphloroglucinol Derivatives from the Branches of Garcinia schomburgkiana - Kaennakam, Sutin; Sukandar, Edwin Risky; Rassamee, Kitiya; Siripong, Pongpun; Santi Tip-pyang (Planta Medica, 2022)
Five undescribed polyprenylated benzoylphloroglucinol derivatives (1 – 5), named garschomcinols A – E, and five known analogues (6 – 10) were isolated from the branches of Garcinia schomburgkiana. Their structures were determined on the basis of 1D and 2D NMR and HRESIMS analyses. The absolute configuration of the bicyclo [3.3.1]nonane core structure of the polyprenylated benzoylphloroglucinols was assigned by comparison of its experimental electronic circular dichroism data with that of related compounds. All isolated compounds were evaluated for their cytotoxicity in vitro against five cancer cell lines. Compound 6 showed potent cytotoxicity against five cancer cell lines including KB, HeLa S3, HT-29, MCF-7, and Hep G2 with IC50 values in the range of 5.05 – 7.03 µM.
Keywords: Garcinia schomburgkiana; Clusiaceae; polyprenylated benzoylphloroglucinols; garschomcinols A – E; cytotoxicity